Strategi Peningkatan Kompetensi Pegawai Bank Perkreditan Rakyat (BPR) - Novi Intan Fandini; Ni Nyoman Sunariani (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACT The purpose of this study was to find out and analyze the strategy of increasing HR competency in the Rural Credit Banks (BPR) of Denpasar City. This study used qualitative research methods. The collection technique used in this study was using the method of interview, observation, and documentation study. Data analysis in this study uses data reduction, data display, and data conclusion drawing/ verification. The results of this study indicate that the strategy of improving HR competencies and the quality of work of each employee can be obtained from the results of the implementation of education and training (training). This can be assessed from changes in attitudes of each employee, knowledge and skills of employees, and the emergence of new innovations that are useful for improving HR competencies, the motivations given by superiors at PT. BPR Bali Dananiaga which plays an important and maximum role in providing the best experience, so that it will improve the performance of employees in the agency. This research can be useful for the leadership of PT. BPR Bali Dananiaga in decision making and also as an important reference to choose the type of education and training (training) that is needed by employees so that what is obtained from the results of the implementation of education and training (training) can be applied in their respective workplaces.